Rat Microglia Cells: Their Culture, Isolation and Phagocytic Activity - Dewi Fatma (Journal of Dentistry Indonesia, 2015)
Microglia were isolated from mixed primary cell cultures of the cerebral cortex from 3day old male Wistar rats. The mechanically dissociated cells were plated in a flask at a density of 107per 300 cm2 and maintained at 37°C in a 10% Co2/90% air atmosphere. After 10-14 days in culture, floating and attached cells on the mixed primary cultured cell layer were isolated by gentle shaking of the flask for 5 min. The resulting cell suspension was transferred to plastic dishes and allowed to adhere at 37°C . To investigate the morphological change of microglia, the cells after 2 days of culture were incubated with biotinylated GSA-1-B4 (10µg/ml) at 4°C for overnight. To detect the phagocytic activity, isolated microglia were incubated with opsonized zymosan (20mgl/ml) for Ih at 37°C and with Giemsa's staining solution for 30 min at room temperature. The results were about 90% of attached cells  had amoeboid and rod-shaped cell bodies with no or a few thick processes. Most of these cells became amoeboid-like cells and showed a number of vacuoles in the cytosol when cultured in the presence of IFN-ɣ+LPS. Both control and IFN-ɣ + LPS – treated cells exhibited the intense phagocytic activity against zymosan particles.